Autism Open Clinical Model (A- O.C.M.) Struttura di un modello clinico integrato per la valutazione ed il trattamento dell'autismo - Flavia Morfini (Marp Edizioni, 2023)
This work starts from the examination of the characteristics of the scientific literature concerning autism disorders and from the analysis of the needs of the autistic subject and his family. It is focuses on the description of an integrated clinical model called Autism Open Clinical Model (A. - O. C. M.). It constitutes the hypothesis of a basic approach with which to face the evaluation and treatment of autism spectrum disorders. The A- O.C.M. represents an open system which, although starting from the integration of three models: applied behavioural analysis, Cognitive-behavioural Therapy and Gestalt Therapy, was designed to be enriched by contributions from other models and settings. It is a clinical model in continuous evolution which therefore constitutes an open system. The aim is to develop a scientific production and clinical practice characterized by a constant and profound work of comparison, integration and dialogue between scholars. It will be highlighted how this aspect, although essential to a scientific discourse, is, however, currently lacking. Therefore, in the light of the state of the art of autism research, the basic structure of the model will be described. Starting from its epistemological premise, principles and characteristics will be defined. Finally, the clinical implications will be investigated.